2017
DOI: 10.3390/ijerph14101153
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Social/Psychosocial Factors and Genetic Variants on Body Mass Index: A Gene-Environment Interaction Analysis in a Longitudinal Setting

Abstract: Obesity, which develops over time, is one of the leading causes of chronic diseases such as cardiovascular disease. However, hundreds of BMI (body mass index)-associated genetic loci identified through large-scale genome-wide association studies (GWAS) only explain about 2.7% of BMI variation. Most common human traits are believed to be influenced by both genetic and environmental factors. Past studies suggest a variety of environmental features that are associated with obesity, including socioeconomic status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…The interactions between SNPs and S. mutans were assessed by including a product term () in the regression models. 50,51 To maximize sample size and power, stratified analyses were not conducted at the genome-wide association analysis stage. 52 …”
Section: Methodsmentioning
confidence: 99%
“…The interactions between SNPs and S. mutans were assessed by including a product term () in the regression models. 50,51 To maximize sample size and power, stratified analyses were not conducted at the genome-wide association analysis stage. 52 …”
Section: Methodsmentioning
confidence: 99%
“…In any case, what these results tend to show is the importance of both genetic and environmental factors and probably their interactions on changes in obesity markers within the family orbit. We also contend that given the evident lack of data on genome-wide association (GWA) and gene-environment interaction studies in all markers (except for BMI), we are not yet able to present a clear picture of what is happening [4244]. Indeed, using BMI data Felix et al [43] GWA study signaled that the direction of the effect size for all 15 single nucleotide polymorphisms (SNPs) was identical in children and in adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, Graff et al [44] showed that obesity susceptibility loci may have a comparatively stronger role during adolescence than adulthood, with variations across race/ethnic subpopulations. Additionally, using European and African American samples, Zhao et al [42] examined social/psychosocial factors that may modify the effect of sets of genetic variants on BMI and reported that socioeconomic status (parental education) was found to modify the genetic effect in the gene/region around SNP rs9540493 on BMI only in European Americans.…”
Section: Discussionmentioning
confidence: 99%
“…16 The previous GWAS meta-analysis for body mass index using the Genetic Epidemiology Research on Adult Health and Aging (GERA) and Genetic Investigation of ANthropometric Traits (GIANT) consortium was used as the replication outcome data, which was available in the GWAS catalog (URL: https://www.ebi.ac.uk/gwas/studies/GCST006368) (Figure 1). 13,20 The meta-analysis included 364,487 samples mostly of European ancestry towards body mass index phenotype (Supplementary Table 2). The GERA data was not included in the previous meta-analysis which provided the genetic instrumental variable, as GERA data was only used for GWAS towards drinking behavior in the meta-analysis.…”
Section: Replication Outcome Datasetmentioning
confidence: 99%